Pengaruh Motivasi dan Beban Kerja Terhadap Kinerja Dosen: Studi Kasus Fakultas Ekonomi dan Bisnis Universitas Bhayangkara Jakarta Raya - Nia Kurniawati; Cahyadi Husadha; Tutiek Yoganingsih (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study aims to determine whether there is an influence of Motivation and Workload on Lecturer Performance at the Faculty of Economics and Business, Management Study Program (S1), Bhayangkara University, Jakarta Raya. This type of research is quantitative. The population and sample in this study were lecturers of the Faculty of Economics and Business, Management Study Program (S1), Bhayangkara University, Greater Jakarta, totaling 51 lecturers and 46 respondents. Data collection techniques by distributing questionnaires. With SEM-PLS analysis technique using SmartPLS 4.0 software for data processing. The findings of the research that has been done show that: 1) Motivation has a positive and significant effect on Lecturer Performance, 46 df <0.05=1.67866, the test results on the P Value of the Motivation variable have a value of 0.008. and 2) Workload has a positive and significant effect on Lecturer Performance, 46 df <0.05=1.67866, the test result on the P Value value of the Workload variable has a value of 0.001.